Whole-body vibration transmission during resistance vibration exercise - Sorrentino, Riccardo G.; Verdel, Nina; Supej, Matej; Ciuha, Ursa; Mekjavic, Igor B. (Frontiers in Sports and Active Living, 2025)
IntroductionResistive exercise combined with whole-body vibration (WBV) and short-arm human centrifugation is being considered as a countermeasure to mitigate muscle and bone loss in astronauts during prolonged space missions. WBV may provide exercise benefits or adverse effects on organs and the lower back. These effects may result from vibration transmitted throughout the body. The objective of this study was to compare vibration transmission (VT) from the ground to the body during resistance vibration exercise (RVE) comprising squat and calf raise performed on a rotational vibration plate. Specifically, we compared VT during RVE in the upright position (URVE) and on a short-arm human centrifuge (artificial gravity, AG) establishing a similar ground reaction force. The latter (AGRVE) is considered a potential countermeasure for microgravity-induced musculoskeletal deconditioning.MethodsFifteen healthy males participated. They were assigned to two groups: one (n = 8) performed URVE at 20% of 1 repetition maximum (RM) squat; the other (n = 7) performed horizontal RVE during AG exposure (AGRVE), with a matching ground reaction force. Both groups were exposed to vibration at 20 Hz and 3–4 mm displacement (RMS value: 4 ± 0.14 g). VT was recorded during two sets of squats and calf raises. Three accelerometers recorded VT at: (i) the platform surface at the feet, (ii) lower back (L5), and (iii) forehead.ResultsIn both conditions, the lower limbs attenuated vibration transmission to the lower back (p < 0.0001). During AGRVE, both VT and pelvis octave-band RMS values were lower compared to URVE in both squat (p = 0.008 and p = 0.01) and calf raise (p = 0.007 and p = 0.01), suggesting potentially greater safety for the lower back.ConclusionDuring RVE, whether in URVE or AGRVE, lower limbs effectively attenuated vibrations, resulting in negligible pelvic exposure. AGRVE may represent a safer alternative to URVE due to reduced transmission to the lower back and adjacent sensitive regions.